Enhanced stability of emulsions made with super‐critical carbon dioxide extruded whey protein concentrate. (16th July 2019) - Javad, Sumera; Gopirajah, Rajamanickam; Rizvi, Syed S. H.
Abstract: Supercritical fluid extrusion (SCFX) with carbon dioxide was used to enhance the functionality of whey protein concentrate containing 80% protein by weight (WPC80) at two (3.0 and 5.4) pH values. Different levels of oil (20, 40, 60, and 80% by weight) and functionalized whey protein (f‐WPC80; 1, 2, and 4% by weight) were used to make emulsions and quantify their characteristics such as emulsion activity index, creaming index, droplet size, and viscosity. Unextruded whey protein (c‐WPC80) and commercial sodium caseinate (NaCas) were used as controls. Results showed that gel‐like emulsions with uniform droplet size distributions were formed by f‐WPC80 (4% by weight) with 80% (by weight) oil which was stable over 3 months of storage at room temperature. Compared to emulsions formed by control c‐WPC80, the f‐WPC80 emulsions exhibited higher viscosity and shear thinning behavior. The minimum protein required for stable emulsion formation (with 80% oil) was found to be 2% by weight for f‐WPC80 and NaCas and 4% by weight in the case of c‐WPC80. The functionalized whey protein provided a better emulsion at low concentrations with good stability at room temperature and may be used as a replacement of sodium caseinate to make nutritionally superior products. Practical applications: Present study showed that functionalized Whey protein concentrate (80% protein) f‐WPC80 was produced by the process of Supercritical carbon dioxide assisted extrusion which changed the structure of native protein. Two functionalized products (with pH 3.0 and 5.4) were obtained in this way. These functionalized proteins formed better oil‐in‐water emulsions which were stable against creaming and sedimentation as compared to emulsions stabilized by native WPC80 and sodium caseinate at very small concentration of protein used. Therefore it is concluded that f‐WPC80 can cover a range of food emulsions where different pH values are required. Lesser amount of stabilizer will be used commercially for emulsions. These functionalized WPC80 products may be used as a replacement of sodium caseinate to make nutritionally superior products with pH 3.0 and 5.4.